Demonstration on the treatment of paper‐making wastewater by a full‐scale IC‐A/O‐membrane reactor system for reclamation. Issue 12 (8th June 2020) - Zhuang, Haifeng; Cheng, Zhong; Shan, Shengdao; Shen, Haitao; Zhao, Bingjun
Abstract: BACKGROUND: The paper‐making industry has developed rapidly in recent years. The paper‐making process consumes much water and generates large amounts of wastewater. The reuse of the produced wastewater helps to save water consumption and reduce environmental pollution. Effective methods to treat and recycle paper‐making wastewater are urgently sought. RESULTS: In this study, the performance of a full‐scale internal circulation–anoxic/oxic (IC‐A/O)–ultrafiltration (UF)–reverse osmosis (RO) membrane system for reclamation and reuse of paper‐making wastewater was investigated. Results showed that the integrated system presented a stable and highly efficient performance. The effluent concentrations of chemical oxygen demand, total organic carbon, biochemical oxygen demand, NH4 + nitrogen and total nitrogen were 12, 4, 0.3, 0.5 and 2.9 mg L −1 . gas chromatographic–mass spectrometric results showed that the organic composition in each process of the IC‐AO‐UF‐RO system varied significantly. Acute biological toxicity was obviously reduced, with an effluent toxic unit value of 3.11. The results of particle size distribution indicated that anaerobic granular sludge (around 3 mm) was formed in an IC reactor. Anaerolinea, Propioniciclava and Thauera were the main contributors to pollutant removal. Advanced treatment by the UF‐RO system achieved complete removal of suspended solids, silt density index and turbidity with little hardness and conductivity in the final effluent, which allowed for reclamation of paper‐making wastewater. CONCLUSION: Water reuse and energy recycling were successfully realized in the built‐up IC‐AO–membrane reactor system. © 2020 Society of Chemical Industry